The Effectiveness of The Board of Directors' Performance and The Moderation Effect of Corporate Risk Management on The Company's Financial Performance - Butar-Butar, Dea Tiara Monalisa; Indrianto, Doni (Global Financial Accounting Journal, 2023)
Purpose – This study aims to analyze the relationship between variables of the Board of Directors (BOD) effectiveness, specifically board size, board independence, and gender with the financial performance of companies measured through Tobin’s Q. The study also considers the role of the chief risk officer as proxy for enterprise risk management (ERM) as moderating variable. Research Method – The data used is sourced from the financial reports of LQ45 listed companies on the Indonesia Stock Exchange for the period 2018-2022 with a total of 44 companies as the sample. The analytical method employed is multiple linear regression using the Eviews software. Findings – The results indicate that board gender and board independence have negative significant effect on Tobin’s Q, while board size has no significant effect. The result of regression test with moderating variables show that the enterprise risk management as a moderating variable has significantly effect of board independence on Tobin’s Q. Implication – The existence board of director has an important and vital role in managing the company’s transactions, determining the company’s management policies, and controlling operations to ensure company’s efficiency. To develop strategies, manage risks, and drive confidence to achieve organizational goals in order to create effectiveness and efficiency, companies san consider establising enterprise risk management. In this study, it is proven that the existence of enterprise risk management can improve the company’s financial performance.